Uncontrolled diabetes mellitus increases risk of infection in patients with advanced cirrhosis. Issue 4 (April 2021) - Rosenblatt, Russell; Atteberry, Preston; Tafesh, Zaid; Ravikumar, Aarti; Crawford, Carl V.; Lucero, Catherine; Jesudian, Arun B.; Brown, Robert S.; Kumar, Sonal; Fortune, Brett E.
Abstract: Background: Diabetes mellitus (DM) is common in patients with cirrhosis and is associated with increased risk of infection. Aim: To analyze the impact of uncontrolled DM on infection and mortality among inpatients with advanced cirrhosis. Methods: This study utilized the Nationwide Inpatient Sample from 1998 to 2014. We defined advanced cirrhosis using a validated ICD-9-CM algorithm requiring a diagnosis of cirrhosis and clinically significant portal hypertension or decompensation. The primary outcome was bacterial infection. Secondary outcomes included inpatient mortality stratified by elderly age (age≥70). Multivariable logistic regression analyzed outcomes. Results: 906, 559 (29.2%) patients had DM and 109, 694 (12.1%) were uncontrolled. Patients who had uncontrolled DM were younger, had less ascites, but more encephalopathy. Bacterial infection prevalence was more common in uncontrolled DM (34.2% vs. 28.4%, OR 1.33, 95% CI 1.29–1.37, p <0.001). Although uncontrolled DM was not associated with mortality, when stratified by age, elderly patients with uncontrolled DM had a significantly higher risk of inpatient mortality (OR 1.62, 95% CI 1.46–1.81). Conclusions: Uncontrolled DM is associated with increased risk of infection, and when combined with elderly age is associated with increased risk of inpatient mortality. Glycemic control is a modifiable target to improve morbidity and mortality in patients with advanced cirrhosis.